PENGEMBANGAN MEDIA COUNTING BOARD BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS 1 SDN JEGULO 1 - asma, yulia; Agustin, Ina (Scholarly Journal of Elementary School, 2024)
This research aims to 1) develop contextual-based Counting Board media, 2) describe the level of validity, level of effectiveness and level of practicality of contextual-based Counting Board media. This type of research is research and development (Research and Development) with the ADDIE model which has five stages, namely analysis, design, development, implementation and evaluation. The instruments used in this research include observation, interviews, questionnaires and tests. The research was carried out at SDN Jegulo 1 involving 23 grade 1 students. The data analysis technique uses questionnaire score calculations, to determine the level of media validity, getting very valid results from the assessment of three validators, namely: material expert validator, media expert validator, and language validator. The level of practicality obtained from data from the results of teacher response questionnaires and student responses by obtaining assessments is very practical to use. Meanwhile, to determine the level of student practicality through student tests in the form of pre-test and post-test with a result of 0.75 calculated using the N-Gain formula so that contextual-based Counting Board media can improve mathematics learning outcomes for addition and subtraction material.